Effect of varieties of Curcuma xanthorrhiza and extraction solvent on total phenolic, total flavonoid content, and antioxidant capacity - GARDA YODI; I MADE ARTIKA; WARAS NURCHOLIS (Society for Indonesian Biodiversity, 2023)
Abstract. Yodi G, Artika IM, Nurcholis W. 2023. Effect of varieties of Curcuma xanthorrhiza and extraction solvent on total phenolic, total flavonoid content, and antioxidant capacity. Biodiversitas 24: 6425-6431. Temulawak (Curcuma xanthorrhiza Roxb.) is widely recognized for its high phytochemical content and antioxidant capacity. Therefore, this study aimed to measure yields, total phenols, total flavonoids, and antioxidant capacity of acetone and ethyl acetate extracts from three varieties of Temulawak, namely Cursina 1, Cursina 2, and Cursina 3. The samples were extracted using the maceration method and evaporated with a rotary vacuum evaporator. In this study, total phenolic and flavonoid contents were analyzed using a colorimetric method, while antioxidant capacity was assessed through DPPH, ABTS, and FRAP assays. The highest acetone and ethyl acetate extract yields were obtained from Cursina 2, i.e., 5.8% and 4.3%, respectively. The highest phenol in the acetone and ethyl acetate extract was from Cursina 2, consisting of 9.55±0.37 mg GAE/g DW and 4.60±0.12 GAE/g DW. The highest flavonoid content in the acetone and ethyl acetate extract was from Cursina 2, i.e., 20.48±0.45 QE/g and 8.59±0.14 mg QE/g DW, respectively. The DPPH method showed that acetone and ethyl acetate extracts of Cursina 2 had the highest antioxidant activities, i.e., 3.28±0.03 ?mol TE/g DW and 2.11±0.04 ?mol TE/g DW, respectively. The highest antioxidant capacity based on the ABTS method was found in the acetone extract of Cursina 2 (148.91±6.10 ?mol TE/g DW) and ethyl acetate extract of Cursina 3 (84.30±5.10 ?mol TE/g DW). The FRAP method showed the highest antioxidant capacity was Cursina 2 acetone extract (115.23±2.30 ?mol TE/g DW) and ethyl acetate extract of Cursina 3 (71.88±1.48 ?mol TE/g DW). These results suggested that acetone is a more suitable solvent for the Cursina 2 variety, while ethyl acetate is more suitable for the Cursina 3 variety.